Political Ambiguity in Chinese Climate Change Discourses. (1st December 2015) - Lo, Alex Y.
Abstract : China's political environment offers limited space for critical debates on domestic politics. In such a constrained environment, people tend to represent and articulate climate change issues without explicitly addressing their political aspects. The aim of this paper is to examine this political ambiguity in climate change discourses. Q methodology was employed to elicit the subjective positions of forty-five young and educated Chinese individuals. Three discourses were extracted: namely, prosaic environmentalism, co-operative economic optimism and actor scepticism. These discourses do not indicate critical intent and deep engagement in the political arguments regarding climate change. This raises concern about the growth of climate citizenship within the country.